Reviews of Environmental Contamination and Toxicology Continuation of Residue Reviews - Ware, George W. (Reviews of Environmental Contamination and Toxicology, 1991)
Reviews of Environmental Contamination and Toxicology publishes authoritative reviews on the occurrence, effects, and fate of pesticide residues and other environmental contaminants. It will keep you informed of the latest significant issues by providing in-depth information in the areas of analytical chemistry, agricultural microbiology, biochemistry, human and veterinary medicine, toxicology, and food technology.